Yloilo as text a critical examination of Alfred McCoy's writings on Iloilo City, Philippines, 1977-2000. - Colago, Dionamie Narisma (2016.)
This undergraduate research examined Alfred McCoy?s portrayal of Iloilo City in his narratives of the city?s history. The New Historical Criticism was used as an approach to present that Alfred McCoy fell into the dilemma of subjectivity in his accounts on Iloilo City from 1977 until 2000. Four significant observations were made from the analysis of his entire texts in his locality: 1) his accounts focused on his characterization of Iloilo City?s transformation from 1855 until 1955, 2) his presentation about Iloilo City was highly stratified and bounded by the dominance of prominent members in the city, 3) his key actors were the elite members of the Ilongo society, 4) the actions of Ilongo individuals were determined by their social classes in Iloilo City. McCoy depicted that Iloilo society is weak, hence portraying it negatively. He only emphasized the foreign rule in Iloilo society and implicitly accounted for the Western dominance such as the Spanish colonial control, British expansion of power, and American dominion in Iloilo City. This research contended that even if developments in the writing of history emerged in the twentieth century, the long standing debate on Orientalism was never a passé. Thus, Alfred McCoy?s texts on Iloilo City accounted for the Orientalist narrative of the city?s history.
Research Paper (Undergraduate, Bachelor of Arts in Political Science-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: McCoy, Alfred W; History -- Iloilo City -- Research